Hodnocení finanční situace podniku a návrhy na její zlepšení - Blahoušková, Simona (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Diplomová práce se zabývá analýzou finanční situace společnosti NEKR SERVIS s. r.o. v období 2003 – 2006 pomocí vybraných metod finanční analýzy. Kromě finanční analýzy je provedena i SWOT analýza, která určuje silné a slabé stránky, nedostatky a příležitosti společnosti NEKR SERVIS s.r.o. a navrhuje možná řešení, která povedou ke zlepšení finanční situace této společnosti v následujících letech.

The diploma thesis focuses on the analysis of the financial situation of NEKR SERVIS s.r.o. company for the years 2003- 2006 through the use of selected methods of financial anylysis. In addition to the financial analysis also a SWOT analysis was undertaken to illustrate the strengths, weaknesses, shortcomings and opportunities of the company. Finally this thesis suggests possible solutions for the improvement of the financial situation of this company in the coming years.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: Finanční analýza; poměrové ukazatele; rozdílové ukazatele; soustavy ukazatelů; rentabilita; investice; účetní výkazy; hodnocení firmy; SWOT analýza.; Financial Analysis; proportion ratios; diferential ratios; ratio systems; profitability; investments; financial statements; company rating; SWOT analysis.